PRELIMINARY SLOPE MAPPING IN CINTARATU VILLAGE, PANGANDARAN, WEST JAVA - Hermanto, Bambang; Putra, Pringgo Kusuma Dwi Noor Yadi; Khoirullah, Nur (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
The shape of a landscape is the result of geological processes in the past as well as human processes at this time. Slope mapping is one way of identifying hazards based on current landforms. Cintaratu Village area is an area that has a unique landscape condition because it has a lot of clastic limestone as a result of the karstification process millions of years ago and is currently experiencing significant developments in infrastructure development. This study aims to see the state of the slope around Cintaratu Village. This research uses a qualitative method that will be described as descriptively. Based on the results, several areas have very steep slopes form by clastic limestones and soils. The mean slope varies from 30° to 90° with a height of up to 30 m.